MANAJEMEN LABA MENGGUNAKAN CLASSIFICATION SHIFTING DAN KUALITAS AUDIT - Debbianita Debbianita; Sylvia Veronica Siregar; Desi Adhariani (University of Merdeka Malang, 2016)
AbstractThis research aims to detect earnings management through classification shifting by classifying core expensesas discontinued operation or special items to increase core earnings. This research also predict that AuditQuality (KAP big 4 or non-big 4) can mitigate earnings management through classification shifting. Samplesof this research are obtained by using purposive sampling from all companies listed in the capital markets ofSingapore, Malaysia, Indonesia, and Philippines. Methods of data analysis used in this research were multiplelinear regression cross section data were processed using statistical software E-views 6.0. Final samples are1551 observations for the year 2012. Results showed that there no classification shifting through discontinuedoperations and special items. Audit Quality is found to be unable to mitigate earnings management throughclassification shifting.